Proceedings of the 2009 Annual Research Conference of the South African Institute of Computer Scientists and Information Techno 2009
DOI: 10.1145/1632149.1632165
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of open source software in business models

Abstract: Free / Libre open source software (FLOSS/OSS) has gained increasing popularity and utilisation in commercial and governmental organisations. Universities like Harvard and Stanford now offer courses on open source as a business and also on how businesses can compete with open source firms. However, very little research has been published in regards to the influence of OSS on business strategies; the use of OSS as a viable business or its value proposition within a commercial entity. The business model, a powerf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…These are important aspects and business drivers for the Tools department as Jenkins and Gerrit constitute the critical parts in Sony Mobile's continuous integration tool chain. From this perspective, a trend may be seen in how the different communities are becoming more professionalized in the sense that the tools make up business critical assets for many of the stakeholders in the communities, which motivates a continuous effort in risk-reduction (Munga et al 2009;Henkel 2006).…”
Section: Testingmentioning
confidence: 99%
“…These are important aspects and business drivers for the Tools department as Jenkins and Gerrit constitute the critical parts in Sony Mobile's continuous integration tool chain. From this perspective, a trend may be seen in how the different communities are becoming more professionalized in the sense that the tools make up business critical assets for many of the stakeholders in the communities, which motivates a continuous effort in risk-reduction (Munga et al 2009;Henkel 2006).…”
Section: Testingmentioning
confidence: 99%
“…Naturally, the user experience on the websites like JIRA would be carefully nurtured. We interviewed one core developer on JBoss community day 19) , who confirmed that the usual way for JBoss developers to handle user issues in the first place. Moreover, shunting external issues to the forum and keeping the issue tracking system more professional in JBossAS helped with the rapid resolution of user issues.…”
Section: Resolution Speed Of Issue Reportsmentioning
confidence: 80%
“…There are also some empirical studies on successful hybrid projects. These enable us to understand how to improve upon existing software development practices, e.g., the analysis of business strategies [1,19] and development methodology [20]. In particular, Wagstrom et al [21] provided an in-depth analysis of commercial involvement in the GNOME and Eclipse software projects, and measured the impact of two kinds of commercial involvement, namely community-focused and product-focused, on the participation http://engine.scichina.com/doi/10.1007/s11432-013-4914-6 of volunteers.…”
Section: Related Workmentioning
confidence: 99%
“…Commercial features: 0 (no) or 1 (yes) based on whether the OSS project offers commercial features or a pro (paid) version. The indicator was based to the work of [18]. 0 is considered a non resilient value.…”
Section: Indicatorsmentioning
confidence: 99%